Aerodynamic Characteristics of Helicopter with Ducted Fan Tail Rotor in Hover under Low-Speed Crosswind - Nahyeon Roh; Sejong Oh; Donghun Park (International Journal of Aerospace Engineering)
The tail rotor of a helicopter operating under low-speed crosswind undergoes highly complex flow due to the interaction between the main rotor, fuselage, and tail rotor system. In this study, numerical simulations have been conducted on the complete configuration of a helicopter with a ducted fan tail rotor system (comprising a main rotor, ducted fan tail rotor, fuselage, and empennage) to analyze the wake interaction in hovering flight under various crosswind directions. The flow characteristics around the tail rotor, the tail rotor thrust, and the yawing moment of the helicopter are investigated and evaluated. The aerodynamic forces are compared with those of a helicopter with an open-type tail rotor. The results indicate that the aerodynamic performance of the ducted fan tail rotor is highly affected by the wakes of both the main rotor and port wing. Nevertheless, the helicopter with a ducted fan tail rotor is observed to be much more directionally stable under various crosswind directions, than that with an open-type tail rotor. This is because the rotor is protected by the fixed part of the tail rotor system in the former case.